Analysis of the regulatory and methodological base of EU COUNTRIES and USA for determining the hygienic standards of carcinogenic substances for the working area (review of the literature and regulatory documents) (Environment & Health, 2024)
The aim of the work was to analyze the current state of determining the regulations of chemical substances, including carcinogens, for the conditions of occupational influence prevention.Research materials and methods: sources of scientific literature, EU directives, materials of the European Air Protection Agency. Methods of empirical and theoretical analysis of scientific information was used.The results. It was shown that international experience in regulating harmful factors in the air of the working area is extremely important for extrapolating their data to the conditions of Ukraine, for which the problem of work environmental pollution is extremely important, especially in view of the probable impact on oncopathological processes among workers. This is due to the fact that the majority of active domestic enterprises of various industries are considered according to the classification of the International Agency for the Study of Cancer as directly carcinogenic to humans. The data are presented, which indicate the constant growth of oncological diseases both among the population as a whole and among working contingents. The work analyzes organizational and methodical approaches to the development of measures to prevent the impact of harmful factors on workers. It has been proven that the main purpose of the regulations of the European Agency for Chemical Compounds is aimed at ensuring a high level of protection of the population and the environment from the harmful effects of chemicals and at promoting the functioning of the internal market through the support of innovative technologies and increasing competitiveness. To solve these issues, a number of declaratory regulations have been developed in the EU countries, which are illustrated by the List of carcinogenic factors and established occupational exposure limits. It has been established that the most effective form of protection for workers is the hygienic regulation of chemical compounds. According to the EU Directives, two types of limits are established: an indicative occupational exposure limit and a limit based on the assumption of a certain risk. Today, limits on the level of concentrations corresponding to the risk of exceeding the risk of developing cancer during life at the level of one case per 10,000 (х10-4) workers are recommended for EU countries. This approach determines the presence of regulations in the EU countries at a lower level compared to domestic hygiene standards. A conclusion is made regarding the need to review the domestic regulatory framework and harmonize it in accordance with EU requirements.